2020
DOI: 10.1002/advs.202002596
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes for Wound Healing: Purification Optimization and Identification of Bioactive Components

Abstract: Human mesenchymal stem cell exosomes have been shown to promote cutaneous wound healing. Their bioactivity is most often attributed to their protein and nucleic acid components, while the function of exosomal lipids remains comparatively unexplored. This work specifically assesses the involvement of lipids and the transmembrane enzyme CD73 in the exosomes' biological activity in stimulating the cutaneous wound healing process. Since exosome preparation processes are not harmonized yet, certain production and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 79 publications
1
51
0
1
Order By: Relevance
“…Our data demonstrated that both BMSC and ADSC-EVs promoted fibroblast and keratinocyte migration in vitro ( Figure 5 A). The ability of EVs to drive keratinocyte and fibroblast migration during wound healing was correlated to their CD73 content [ 52 ] and previous reports demonstrated that BMSC and ADSC express similar level of CD73 [ 7 ]. Here, we demonstrated that BMSC and ADSC-EVs express similar levels of CD73 by FACS analysis ( Figure 1 C), possibly explaining their similar effect on keratinocyte and fibroblast migration in diabetic wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that both BMSC and ADSC-EVs promoted fibroblast and keratinocyte migration in vitro ( Figure 5 A). The ability of EVs to drive keratinocyte and fibroblast migration during wound healing was correlated to their CD73 content [ 52 ] and previous reports demonstrated that BMSC and ADSC express similar level of CD73 [ 7 ]. Here, we demonstrated that BMSC and ADSC-EVs express similar levels of CD73 by FACS analysis ( Figure 1 C), possibly explaining their similar effect on keratinocyte and fibroblast migration in diabetic wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MSC-derived exosomes have broad prospects as a therapeutic agent. It is worth noting that although MSC exosomes avoid the risks of immunogenicity and tumorigenicity that are associated with cell transplantation, there are still many problems associated with application in the clinical setting, including production standards (e.g., culture separation, cell phenotype, quantification, and positioning tracking after infusion) and the monitoring of efficacy ( 131 ). The determination of clinical indications for different diseases, especially the production of standard dosage in the field of organ transplantation, is a problem that needs to be solved urgently.…”
Section: Dose Issues and Commercial Production Of Msc-derived Exosomementioning
confidence: 99%
“…WJSMC exosomes were defined as positive for CD9, CD63, and CD73 [33]. Cytokine TNF-α stimulation not only increased the amount of exosome secreted from gingivaderived MSCs but also enhanced the exosomal expression of CD73 [34].…”
Section: Perspectives: Other Exo-regulators Underlay Wjmsc-mediated Tmentioning
confidence: 99%